A preparation method of polyolefin fiber and its product and application

By modifying and pretreating ceramic fibers and uniform dispersion, the problems of high viscoelasticity and uneven dispersion of polyolefin fibers are solved, which significantly improves its anti-cutting performance and comfort, and achieves higher anti-cutting performance and feel optimization .

CN116427047BActive Publication Date: 2025-01-14HUIHONG NANTONG SAFETY PRODS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310399078.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-14
Publication Date
2025-01-14
Estimated Expiration
2043-04-14

AI Technical Summary

Technical Problem

The existing polyolefin fibers have high viscoelasticity and uneven dispersion of filling modified materials, resulting in average cutting resistance and limited improvement in hand feel and comfort.

Method used

The ceramic fiber is modified and pretreated by mixed treatment liquid of silane coupling agent, dispersant and organic solvent, and uniformly dispersed nano-scale alumina, micro-scale alumina, nano-scale silica and micro-scale two in polyolefin fibers. Silicon oxide mixed ceramic fibers form a complete crystal structure and high Mohs hardness through reasonable proportions and process parameters, thereby improving the dispersion and compatibility of the fibers.

Benefits of technology

It significantly improves the anti-cutting performance, feel and comfort of polyolefin fibers, enhances the strength, wear resistance, softness, hygroscopicity and breathability of the fibers, and ensures uniform dispersion and stable production of the fibers.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of polyolefin fiber, its product and application, and relates to the technical field of fiber production. The specific steps of the preparation method are as follows: S1, mixing a silane coupling agent, a dispersant and an organic solvent to obtain a treatment liquid; S2, uniformly dispersing the treatment liquid on fully dried ceramic fibers, and stirring at high speed, wherein the ceramic fibers are a mixture of nano-alumina, micron-alumina, nano-silicon dioxide and micron-silicon dioxide; S3, premixing polyolefin powder and treated ceramic fibers at high speed to obtain an anti-cutting functional masterbatch, and then melt spinning to obtain polyolefin fibers. The invention greatly improves the strength, wear resistance, softness, comfort, hygroscopicity and air permeability of the prepared polyolefin fibers, thereby greatly improving the anti-cutting performance, feel and comfort of the polyolefin fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fiber production, and in particular to a method for preparing polyolefin fiber and a product and application thereof. Background Art

[0002] The most commonly used raw material for cut-resistant fabrics is polyolefin fiber, which refers to a type of synthetic fiber composed of linear macromolecules polymerized from olefins. Polyethylene fiber, polypropylene fiber, etc. are relatively common polyolefin fibers. Traditional cut-resistant fabrics are often woven from polyolefin fibers and hard fibers such as glass fiber and steel wire. This type of product has a certain effect on cut resistance, but it is not ideal when used in contact with the human body. It has a poor feel and low comfort. At the same time, the production process is cumbersome and costly. Therefore, there is an urgent need for a body fiber with cut-resistant function.

[0003] Relevant research in the prior art on the preparation of polyolefin fibers with anti-cutting function, such as patent application CN108277546A, a method for preparing cut-resistant polyethylene fibers, etc., can directly prepare modified polyolefin fibers, so that a certain anti-cutting performance can be achieved without the need for subsequent composite hard fibers, etc. However, the prior art still has the problem of uneven dispersion of the filling modified material when the viscoelasticity of the polyolefin fibers is high, so that the anti-cutting performance of the prepared polyolefin fibers is still average. At the same time, the improvement of the feel and comfort of the polyolefin fibers prepared by the prior art is still limited.

[0004] Therefore, a new technical solution is needed to solve the above technical problems. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing polyolefin fibers, products and applications thereof, so as to solve the technical problems raised in the above-mentioned background technology that the prior art still has the problem of uneven dispersion of filling and modifying materials when the viscoelasticity of the polyolefin fibers is high, so that the anti-cutting performance of the prepared polyolefin fibers is still average, and at the same time, the improvement of the feel and comfort of the polyolefin fibers prepared by the prior art is still limited.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a polyolefin fiber, the specific steps of which are as follows:

[0008] S1. Mixing a silane coupling agent, a dispersant and an organic solvent to obtain a treatment liquid, wherein the silane coupling agent is a mixture of at least two of silane coupling agent KH-602, silane coupling agent KH550, silane coupling agent KH540 and silane coupling agent YDH-151 in any proportion with methylphenyldimethoxysilane, and the dispersant is a mixture of sodium silicate and calcium carbonate in any proportion;

[0009] S2, dispersing the treatment liquid evenly on the fully dried ceramic fiber, and stirring at a temperature of 60-80°C and a high speed of 1800-2200 rpm for 120-200 minutes, wherein the ceramic fiber is a mixture of nano-alumina, micron-alumina, nano-silicon dioxide and micron-silicon dioxide, specifically, in each portion of the fully dried ceramic fiber, the mass fractions of nano-alumina and nano-silicon dioxide are 3-10 parts respectively, the mass fractions of micron-alumina and micron-silicon dioxide are 40-50 parts respectively, the average particle size of nano-alumina and nano-silicon dioxide is 30-70nm, the average particle size of micron-alumina and micron-silicon dioxide is 1-5μm, and the average length of micron-alumina and micron-silicon dioxide is 1-50μm;

[0010] S3, premixing the polyolefin powder and the treated ceramic fiber at high speed to obtain the anti-cutting functional masterbatch, and then melt spinning to obtain the polyolefin fiber. Specifically, the polyolefin powder and the treated ceramic fiber are premixed in a high-speed mixer at 90-100° C. and 400-500 rpm for 1.5-2.5 hours to obtain the anti-cutting functional masterbatch, and then the anti-cutting functional masterbatch is melt-extruded through a twin-screw extruder, and after the melt is formed into a fine flow through a spinneret hole, it is sequentially cooled by side blowing, stretched, heat-set and wound to obtain the polyolefin fiber;

[0011] Furthermore, the mass of the silane coupling agent is 5% to 15% of the mass of the fully dried ceramic fiber, the mass of the dispersant is 2% to 4% of the mass of the fully dried ceramic fiber, and the mass ratio of the fully dried ceramic fiber to the polyolefin powder is 1:18 to 20.

[0012] In a second aspect, the present invention provides polyolefin fibers obtained by the above preparation method.

[0013] In a third aspect, the present invention provides the use of the polyolefin fiber obtained by the above preparation method in cut-resistant fabrics.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] 1. The ceramic fiber in the present invention is a mixture of nano-alumina, micron-alumina, nano-silicon dioxide and micron-silicon dioxide. The ceramic fiber is obtained by mixing two phases of alumina and silicon dioxide, so that the interface bonding is good. When the ceramic fiber with high stability is introduced into the polyolefin fiber, it can be dispersed more evenly in the polyolefin fiber. At this time, under the synergistic effect of the superior characteristics of alumina and silicon dioxide, the strength, wear resistance, softness, comfort, hygroscopicity and air permeability of the prepared polyolefin fiber can be greatly improved, thereby greatly improving the anti-cutting performance, feel and comfort of the polyolefin fiber. On this basis, the present invention uses a treatment liquid mixed with a silane coupling agent, a dispersant and an organic solvent to modify and pre-treat the ceramic fiber, which can effectively improve the compatibility of the ceramic fiber with the polyolefin powder, so that the dispersion uniformity of the ceramic fiber in the polyolefin fiber is fully guaranteed, and finally further improve the anti-cutting performance, feel and comfort of the polyolefin fiber;

[0016] 2. The present invention is based on the ceramic fiber being a mixture of nano-alumina, micron-alumina, nano-silicon dioxide and micron-silicon dioxide. By rationally controlling the ratio of nano-alumina, micron-alumina, nano-silicon dioxide and micron-silicon dioxide and their respective parameters, the mixed ceramic fiber forms a perfect crystal structure and a high Mohs hardness, effectively improving the apparent hardness and microscopic bending strength of the ceramic fiber, thereby achieving a better stress dispersion effect in the polyolefin fiber, and ultimately further improving the anti-cutting performance of the polyolefin fiber; in addition, the present invention rationally controls the addition amount of ceramic fiber and polyolefin powder, i.e., the proportion of anti-cutting functional masterbatch, so that the spinning process is smooth and the spinning quality is stable, thereby further comprehensively improving the overall performance of the polyolefin fiber, and improving the anti-cutting performance, hand feel and comfort of the polyolefin fiber;

[0017] 3. The silane coupling agent in the present invention is a mixture of at least two of silane coupling agent KH-602, silane coupling agent KH550, silane coupling agent KH540 and silane coupling agent YDH-151 and methylphenyldimethoxysilane. The dispersant is a mixture of two inorganic binders, sodium silicate and calcium carbonate. The two cooperate with each other and work together to have excellent dispersibility for ceramic fibers mixed with alumina and silica, which can prevent agglomeration in the subsequent spinning process, ensure continuous and stable production of polyolefin fibers, and finally further ensure the overall performance of the polyolefin fibers, and ensure the anti-cutting performance, feel and comfort of the polyolefin fibers. DETAILED DESCRIPTION

[0018] The following examples are used to further illustrate the content of the present invention, but do not limit the application of the present invention.

[0019] The "parts" in the examples are all parts by weight. Embodiment 1:

[0020] Preparation of cut-resistant fabric:

[0021] S1, randomly mixing at least two of silane coupling agent KH-602, silane coupling agent KH550, silane coupling agent KH540 and silane coupling agent YDH-151 with methylphenyldimethoxysilane to obtain a silane coupling agent, randomly mixing sodium silicate and calcium carbonate to obtain a dispersant, and then taking 0.25 parts of the silane coupling agent, 0.1 parts of the dispersant and anhydrous ethanol to mix to obtain a treatment liquid;

[0022] S2. Add 5 parts of fully dried ceramic fibers into a VC high-speed humidifying mixer (each part of fully dried ceramic fibers contains 3 parts of nano-alumina with an average particle size of 30-70 nm, 3 parts of nano-silicon dioxide with an average particle size of 30-70 nm, 47 parts of micron-sized alumina with an average particle size of 1-5 μm and an average length of 1-50 μm, and 47 parts of micron-sized silicon dioxide with an average particle size of 1-5 μm and an average length of 1-50 μm);

[0023] S3, uniformly dispersing the treatment solution obtained in step S1 on the ceramic fiber in step S2, and stirring at a high speed of 2000 rpm at a temperature of 60° C. for 2 hours;

[0024] S4, taking 95 parts of polyolefin powder and the ceramic fiber treated in step S3, mixing them uniformly in a high-speed mixer at a temperature of 95° C. and 450 rpm for 2 hours to obtain a cut-resistant masterbatch;

[0025] S5, melt-extrude the anti-cutting functional masterbatch obtained in step S4 through a twin-screw extruder, and form a melt stream through a spinneret hole, and then sequentially cool, stretch, heat-set and wind the melt stream to obtain a polyolefin fiber;

[0026] S6. Weaving the obtained polyolefin fibers to make cut-resistant fabrics such as glove blanks. Embodiment 2:

[0027] Preparation of cut-resistant fabric:

[0028] S1, randomly mixing at least two of silane coupling agent KH-602, silane coupling agent KH550, silane coupling agent KH540 and silane coupling agent YDH-151 with methylphenyldimethoxysilane to obtain a silane coupling agent, randomly mixing sodium silicate and calcium carbonate to obtain a dispersant, and then taking 0.75 parts of the silane coupling agent, 0.2 parts of the dispersant and anhydrous ethanol to mix to obtain a treatment liquid;

[0029] S2. Add 5 parts of fully dried ceramic fibers into a VC high-speed humidifying mixer (each part of fully dried ceramic fibers contains 10 parts of nano-alumina with an average particle size of 30-70 nm, 10 parts of nano-silicon dioxide with an average particle size of 30-70 nm, 50 parts of micron-sized alumina with an average particle size of 1-5 μm and an average length of 1-50 μm, and 50 parts of micron-sized silicon dioxide with an average particle size of 1-5 μm and an average length of 1-50 μm);

[0030] S3, uniformly dispersing the treatment solution obtained in step S1 on the ceramic fiber in step S2, and stirring at a high speed of 2200 rpm at a temperature of 80° C. for 100 minutes;

[0031] S4, taking 100 parts of polyolefin powder and the ceramic fiber treated in step S3, mixing them uniformly in a high-speed mixer at a temperature of 90° C. and 500 rpm for 1.5 hours to obtain a cut-resistant masterbatch;

[0032] S5, melt-extrude the anti-cutting functional masterbatch obtained in step S4 through a twin-screw extruder, and form a melt stream through a spinneret hole, and then sequentially cool, stretch, heat-set and wind the melt stream to obtain a polyolefin fiber;

[0033] S6. Weaving the obtained polyolefin fibers to make cut-resistant fabrics such as glove blanks. Embodiment 3:

[0034] Preparation of cut-resistant fabrics:

[0035] S1, randomly mixing at least two of silane coupling agent KH-602, silane coupling agent KH550, silane coupling agent KH540 and silane coupling agent YDH-151 with methylphenyldimethoxysilane to obtain a silane coupling agent, randomly mixing sodium silicate and calcium carbonate to obtain a dispersant, and then taking 0.5 parts of the silane coupling agent, 0.15 parts of the dispersant and anhydrous ethanol to mix to obtain a treatment liquid;

[0036] S2. Add 5 parts of fully dried ceramic fibers into a VC high-speed humidifying mixer (each part of fully dried ceramic fibers contains 5 parts of nano-alumina with an average particle size of 30-70 nm, 5 parts of nano-silicon dioxide with an average particle size of 30-70 nm, 40 parts of micron-sized alumina with an average particle size of 1-5 μm and an average length of 1-50 μm, and 40 parts of micron-sized silicon dioxide with an average particle size of 1-5 μm and an average length of 1-50 μm);

[0037] S3, uniformly dispersing the treatment liquid obtained in step S1 on the ceramic fiber in step S2, and stirring at a high speed of 1800 rpm at a temperature of 70° C. for 150 minutes;

[0038] S4, taking 90 parts of polyolefin powder and the ceramic fiber treated in step S3, uniformly mixing them in a high-speed mixer at a temperature of 100° C. and a speed of 400 rpm for 2.5 hours to obtain a cut-resistant masterbatch;

[0039] S5, melt-extrude the anti-cutting functional masterbatch obtained in step S4 through a twin-screw extruder, and form a melt stream through a spinneret hole, and then sequentially cool, stretch, heat-set and wind the melt stream to obtain a polyolefin fiber;

[0040] S6. Weaving the obtained polyolefin fibers to make cut-resistant fabrics such as glove blanks.

[0041] Comparative Example 1:

[0042] Preparation of cut-resistant fabrics:

[0043] S1. Mix at least two of silane coupling agent KH-602, silane coupling agent KH550, silane coupling agent KH540 and silane coupling agent YDH-151 with methylphenyldimethoxysilane to obtain a silane coupling agent, mix sodium silicate and calcium carbonate to obtain a dispersant, and then mix 0.05 parts of the silane coupling agent and 0.02 parts of the dispersant with anhydrous ethanol to obtain a treatment liquid;

[0044] S2. Add 10 parts of fully dried ceramic fibers into a VC high-speed humidifying mixer (each part of fully dried ceramic fibers contains 3 parts of nano-alumina with an average particle size of 30-70 nm, 3 parts of nano-silicon dioxide with an average particle size of 30-70 nm, 47 parts of micron-sized alumina with an average particle size of 1-5 μm and an average length of 1-50 μm, and 47 parts of micron-sized silicon dioxide with an average particle size of 1-5 μm and an average length of 1-50 μm);

[0045] S3, uniformly dispersing the treatment solution obtained in step S1 on the ceramic fiber in step S2, and stirring at a high speed of 2000 rpm at a temperature of 60° C. for 2 hours;

[0046] S4, taking 95 parts of polyolefin powder and the ceramic fiber treated in step S3, mixing them uniformly in a high-speed mixer at a temperature of 95° C. and 450 rpm for 2 hours to obtain a cut-resistant masterbatch;

[0047] S5, melt-extrude the anti-cutting functional masterbatch obtained in step S4 through a twin-screw extruder, and form a melt stream through a spinneret hole, and then sequentially cool, stretch, heat-set and wind the melt stream to obtain a polyolefin fiber;

[0048] S6. Weaving the obtained polyolefin fibers to make cut-resistant fabrics such as glove blanks.

[0049] Comparative Example 2:

[0050] Preparation of cut-resistant fabric:

[0051] S1. Mix at least two of silane coupling agent KH-602, silane coupling agent KH550, silane coupling agent KH540 and silane coupling agent YDH-151 with methylphenyldimethoxysilane to obtain a silane coupling agent, mix sodium silicate and calcium carbonate to obtain a dispersant, and then mix 0.05 parts of the silane coupling agent and 0.02 parts of the dispersant with anhydrous ethanol to obtain a treatment liquid;

[0052] S2. Add 15 parts of fully dried ceramic fibers into a VC high-speed humidifying mixer (each part of fully dried ceramic fibers contains 3 parts of nano-alumina with an average particle size of 30-70 nm, 3 parts of nano-silicon dioxide with an average particle size of 30-70 nm, 47 parts of micron-sized alumina with an average particle size of 1-5 μm and an average length of 1-50 μm, and 47 parts of micron-sized silicon dioxide with an average particle size of 1-5 μm and an average length of 1-50 μm);

[0053] S3, uniformly dispersing the treatment solution obtained in step S1 on the ceramic fiber in step S2, and stirring at a high speed of 2000 rpm at a temperature of 60° C. for 2 hours;

[0054] S4, taking 95 parts of polyolefin powder and the ceramic fiber treated in step S3, mixing them uniformly in a high-speed mixer at a temperature of 95° C. and 450 rpm for 2 hours to obtain a cut-resistant masterbatch;

[0055] S5, melt-extrude the anti-cutting functional masterbatch obtained in step S4 through a twin-screw extruder, and form a melt stream through a spinneret hole, and then sequentially cool, stretch, heat-set and wind the melt stream to obtain a polyolefin fiber;

[0056] S6. Weaving the obtained polyolefin fibers to make cut-resistant fabrics such as glove blanks.

[0057] The glove blanks prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested using a TDM-100 glove cut resistance tester. The performance grades of the glove blanks prepared in Examples 1 to 3 can reach the American standard ASTM cut resistance grade A2 and above, the European standard ISO grade B and above, the performance grade of the glove blank prepared in Comparative Example 1 is the American standard ASTM cut resistance grade A3, the European standard ISO grade C, and the performance grade of the glove blank prepared in Comparative Example 2 is the American standard ASTM cut resistance grade A3, the European standard ISO grade D; at the same time, the glove blanks prepared in Examples 1 to 3 are very soft and have no roughness to the touch, while the glove blanks prepared in Comparative Examples 1 to 2 are relatively hard and have a roughness to the touch.

[0058] In addition, through research and comparison, it was found that when the mass ratio of ceramic fiber to polyolefin powder is 1:19, and the speed of the high-speed mixer used for premixing the anti-cut functional masterbatch is 450 rpm, the temperature is 95°C, and the time is 2h, the obtained polyolefin fiber and even the anti-cut fabric have excellent anti-cut performance and soft feel. At the same time, the spinning process is normal and the fiber quality is stable.

[0059] The present invention has no special limitation on the spinneret holes used for spinning, and conventional spinnerets in the art can be used.

[0060] The present invention has no particular limitation on the methods of melt extrusion, side-blowing cooling, stretching, heat setting, winding and weaving, and methods well known to those skilled in the art may be used.

[0061] In the present invention, unless otherwise specified, the raw materials used are all commercially available products.

Claims

1. A method for preparing polyolefin fiber, characterized in that: The specific steps are as follows: S1, mixing a silane coupling agent, a dispersant and an organic solvent to obtain a treatment liquid; S2, evenly dispersing the treatment liquid on the fully dried ceramic fiber, and stirring at a high speed of 1800 to 2200 rpm; S3, premixing the polyolefin powder and the treated ceramic fiber at a speed of 400 to 500 rpm and a temperature of 90 to 100° C. for 1.5 to 2.5 hours to obtain a cut-resistant masterbatch, and then melt spinning the masterbatch to obtain the polyolefin fiber; The mass of the silane coupling agent is 5% to 15% of the mass of the fully dried ceramic fiber, the mass of the dispersant is 2% to 4% of the mass of the fully dried ceramic fiber, the mass ratio of the fully dried ceramic fiber to the polyolefin powder is 1:18 to 20, and the ceramic fiber is a mixture of nano-alumina, micron-alumina, nano-silicon dioxide and micron-silicon dioxide; In each portion of the fully dried ceramic fiber, the mass fractions of nano-alumina and nano-silicon dioxide are 3 to 10 parts respectively, and the mass fractions of micron-sized alumina and micron-sized silicon dioxide are 40 to 50 parts respectively; The average particle size of the nano-alumina and nano-silicon dioxide is 30-70 nm, the average particle size of the micron-alumina and micron-silicon dioxide is 1-5 μm, and the average length of the micron-alumina and micron-silicon dioxide is 1-50 μm; The organic solvent is anhydrous ethanol, the silane coupling agent is a mixture of at least two of silane coupling agent KH-602, silane coupling agent KH550, silane coupling agent KH540 and silane coupling agent YDH-151 with methylphenyldimethoxysilane in any proportion, and the dispersant is a mixture of sodium silicate and calcium carbonate in any proportion.

2. The method for preparing a polyolefin fiber according to claim 1, characterized in that: In step S2, the stirring temperature is 60 to 80°C, and the stirring time is 100 to 150 minutes.

3. The method for preparing a polyolefin fiber according to claim 1, characterized in that: The specific operation process of step S3 is as follows: first, the polyolefin powder and the treated ceramic fiber are premixed in a high-speed mixer to obtain an anti-cutting functional masterbatch, and then the anti-cutting functional masterbatch is melt-extruded through a twin-screw extruder, and after the melt is formed into a fine flow through the spinneret hole, it is sequentially cooled by side blowing, stretched, heat-set and wound to obtain polyolefin fiber.

4. A polyolefin fiber obtained by the preparation method according to any one of claims 1 to 3.

5. Use of the polyolefin fiber obtained by the preparation method according to any one of claims 1 to 3 in cut-resistant fabrics.

Citation Information

Patent Citations

  • Preparation method of anti-cutting polyethylene fibers

    CN108277546A

  • Filling reinforced polypropylene composite containing ceramic fibers and preparation method thereof

    CN102108154A

  • Cut-resistant polyethylene composite fiber and preparation method thereof

    CN108004603A